The Revolution of Shex Aubaid Allah Al Nahri in Akhter Newspaper 1880-1883 - Yousif, Fakhir H. (Humanities Journal of University of Zakho, 2018)
Iranian newspaper Akhter is one of the significant newspaper that have a great role in journalism, it is considered one of the most reliable newspaper in this field. The newspaper’s main emphasis is on( The Revolution of Shex Aubaid Allah Al Nahri 1880-1883 in Akhter newspaper)specifically educating readers on new information about this revelation. Therefor, we find that the Akhter Newspaper contains critical information about revolution, particularly how the revolution began. For this reason this Newspaper is a significant source for this revolution. It covered the cause of the revolution, Shex Aubaid Allah in Russo- Ottmanwar(1877.1878), as well as his battle with the Iranian army. The reasons for the decline, opinions of the international community about this revolution.